Effects of in ovo Administration of L-carnitine on Hatching Events and Juvenile Performance of Layer-type Chick - Nouboukpo, K.E.; Tona , K.; Kamers, B.; Everaert, N.; Willemsen, H.; Onagbesan, O.M.; Gbeassor, M.; Decuypere, E. (International Journal of Poultry Science, 2010)
The effects of in ovo injection of L-carnitine on hatchability and juvenile performance of 360 layer-type chicks were investigated. Fertilized eggs were injected in air chamber with L-carnitine (500 and 1000 μmol) dissolved in 0.9% of Saline (NaCl) at d 18 of incubation. Two control groups (non-injected and injected with 0.9% of Saline were also included. Hatched chicks was recorded after every 4 h, beginning at 490 h of incubation and ending at 514 h, for incubation length and hatching spread determination. At the end of incubation, hatched chicks were recorded according to treatment for determination of hatchability. At 3, 7 and 14 d post-hatch, chick body weight (BW) and morbidity were recorded. Also, at d 3 and 7 post-hatch, 14 birds from each of 2 replicate groups within each treatment were used for intestine and yolk sac weight determination. Results indicate that BW, hatchability, or relative intestine weights were not affected by treatment. However, incubation length was longer while hatching spread was shorter in L-carnitine groups compared to control groups. Yolk sac relative weight was decreased by treatment with L-carnitine (P < 0.05). Also, the percentage of chicks showing morbidity sign was lower in L-carnitine treated groups from d 7 onwards. The results of the present study suggest that in ovo injection of L-carnitine at d 18 of incubation delayed hatching time but resulted in narrower hatching spread, faster utilization of yolk sac content and improved morbidity.